The Assessment of CD56 and CD117 Expressions at the Time of the Diagnosis in Multiple Myeloma Patients - Funda Ceran; Mesude Falay; Simten Dağdaş; Gülsüm Özet (Turkish Journal of Hematology, 2017)
Objective: The purpose of this study is to investigate the relationship between the CD56 and CD117 expressions and the clinical and laboratory findings in multiple myeloma (MM) patients. Materials and Methods: Analyses of multiparametric flow cytometry data obtained from the diagnostic bone marrow aspirations of a total of 34 newly diagnosed MM patients were assessed retrospectively. CD56 and CD117 expressions of the patients were compared with their stages and clinical parameters. The staging was performed according to the International Staging System (ISS). Results: Of the patients, 58.8% had ISS stage 1-2 MM while 41.2% had stage 3 MM. The number of CD56-positive patients was 29, whereas the number of CD117-positive patients was 13. There was no statistical difference between the CD56 and CD117 expressions and extramedullary involvement and lytic bone lesions. The median beta-2 microglobulin level was higher in the CD117-negative group (p=0.047). CD56 and CD117 expression levels were found to be lower in advanced-stage patients than in early-stage ones (p=0.026 and p=0.017). The lactate dehydrogenase (LDH) levels were high in advanced-stage patients, and an inverse relationship was found between LDH level and CD117 expression. Conclusion: Our findings that the CD56 and CD117 expression levels are lower in advanced stages than earlier stages and that LDH level and CD117 expression have an inverse relationship in patients with newly diagnosed MM suggest that CD56 and CD117 expressions may be prognostic markers for MM.